African Literature and The Protest Novel: Neo-Nationalism in Ngugi Wa Thiong’o’s Weep Not Child (British Journal of Multidisciplinary and Advanced Studies, 2023)
Every literary writer belongs to a particular society; he writes to reflect the conditions of that society. Therefore, African literature captures the African temperament. This paper attempts an analysis of Ngugi Wa Thiong’o’s Weep Not Child. Colonisation turns people into objects in order for the colonialists to facilitate their manipulation and the handing over power to Africans with a hope that this group of Africans will change the cause of events. The inability of these leaders to perform to expectation leading to a period of transition from colonialism to neo-colonialism necessitated the protests in most African novels. This paper explores the African literature written from the African point of view. It explores what inspires the Africans to protest through their literary works. The origin and trends in African literature from the ancient to the stage of protest is also discussed. The paper uses the eco-criticism framework to focus on the protest element in Ngugi’s Weep Not Child. It exposes the forceful acquisition and abuse of power on the social and political life of the entire citizens. It looks at Ngotho who protests against the inhumanisation and exploitation from the white counterpart, turning them into slaves. It further examines the critical analysis of the novel, viewing the elements that make the novel a protest fiction. Finally, the paper pins down the work of this great African writer as a protest based on its contents.